2019
DOI: 10.24230/kjiop.v32i3.265-295
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotional labor(surface acting, deep acting) and job burnout on job satisfaction among securities branch clerks

Abstract: The purpose of this study is to examine the moderated mediating effect of emotional intelligence on emotional labor(surface acting, deep acting) and job burnout on job satisfaction among securities branch clerks. A total of 288 securities clerks were asked to complete the questionnaires and the data were analyzed using SPSS 23.0 and Mplus 7.0. The results were as follows. First, surface acting had no significant effect on job satisfaction. Seocond, deep acting had significantly positive effect on job satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Investigations into the effects of EL have produced mixed results. Some studies have found that deep acting positively influences workers’ attitudes and behaviors by enhancing work efficiency and job satisfaction through the understanding of required display rules [ 24 27 ]. However, other studies have found no relationship between deep acting and emotional exhaustion or have suggested that it increases emotional exhaustion [ 28 ] and JB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the effects of EL have produced mixed results. Some studies have found that deep acting positively influences workers’ attitudes and behaviors by enhancing work efficiency and job satisfaction through the understanding of required display rules [ 24 27 ]. However, other studies have found no relationship between deep acting and emotional exhaustion or have suggested that it increases emotional exhaustion [ 28 ] and JB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%